2015
DOI: 10.3389/fpls.2015.00859
|View full text |Cite
|
Sign up to set email alerts
|

Beyond plant defense: insights on the potential of salicylic and methylsalicylic acid to contain growth of the phytopathogen Botrytis cinerea

Abstract: Using Botrytis cinerea we confirmed in the present work several previous studies showing that salicylic acid, a main plant hormone, inhibits fungal growth in vitro. Such an inhibitory effect was also observed for the two salicylic acid derivatives, methylsalicylic and acetylsalicylic acid. In marked contrast, 5-sulfosalicylic acid was totally inactive. Comparative proteomics from treated vs. control mycelia showed that both the intracellular and extracellular proteomes were affected in the presence of salicyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 137 publications
2
11
1
6
Order By: Relevance
“…The protein bands obtained from SA treated mycelia of P . microspora were similar to 2.5 mM SA treated protein spots previously reported in the fungus Botrytis cinerea [61] with clear matches of protein bands at 14, 19, 35, 44, and 56 KDa obtained in this study [61]. Further, we observed that SA induced protein expression related to the lipid metabolism and tricarboxylic acid (TCA) pathway (Fig 8).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The protein bands obtained from SA treated mycelia of P . microspora were similar to 2.5 mM SA treated protein spots previously reported in the fungus Botrytis cinerea [61] with clear matches of protein bands at 14, 19, 35, 44, and 56 KDa obtained in this study [61]. Further, we observed that SA induced protein expression related to the lipid metabolism and tricarboxylic acid (TCA) pathway (Fig 8).…”
Section: Resultssupporting
confidence: 89%
“…Moreover, BLAST search against B . cinerea peptide sequence confirmed the presence of biosynthetic enzymes involved in the function of virulence factor (19-kDa protein), immunity and defense (19-kDa protein), TCA pathway (34.6-kDa protein), disease/defence (34.5-kDa protein), lipid metabolism (35.2-kDa and 56.1-kDa proteins), carbohydrate metabolism (44.1 kDa), nucleic acid metabolism (45.7-kDa protein), protein metabolism and modification (55.2-kDa protein) [61].…”
Section: Resultsmentioning
confidence: 99%
“…Together, these findings show that a central regulator of the plant immune system, largely uncharacterized in roots, directly influences the root microbiota composition (Lebeis et al, 2015). Consistent with this, exogenous SA and derivatives proved able to inhibit the growth of B. cinerea in vitro (Dieryckx et al, 2015). Similarly, several studies showed that ABA exhibits antifungal activity in plants (Khedr et al, 2018).…”
Section: Phytohormonessupporting
confidence: 60%
“…Proteomics has emerged as a powerful tool for understanding the molecular mechanism of plant-pathogen interactions (Imam et al, 2017 ). Using proteomics, the response of B. cinerea to plant-based elicitors and hormones (Dieryckx et al, 2015 ; Liñeiro et al, 2016 ), and the in vitro secretome of B. cinerea related to pathogenesis (González-Fernández et al, 2015 ) have been characterized. In general, proteomic analyses of plant hosts in response to fungal pathogens have been widely reported in recent years.…”
Section: Introductionmentioning
confidence: 99%